Socialization of Squid Nugget Making to Increase Creativity in Batu Bara Regency - Budhi Santri Kusuma; Dede Ibrahim Muthawali; Zainuddin Ginting; Zetta Fazira; Desi Sri Pasca Sari Sembiring (Edujavare Publishing, 2024)
Indonesia has great potential in fisheries, including marine products such as squid, especially in Batu Bara Regency. However, the use of squid by coastal communities is still limited to simple processing, so the economic value of this product has yet to be optimal. This socialization program for making squid nuggets aims to increase people's creativity in processing squid into products with high selling value. The service method used is the Community-Based Research (CBR) approach. This program actively involves the community in the entire process, from planning to evaluation, to ensure the relevance and sustainability of the program using this approach, including technical training for making squid nuggets, recipe innovation sessions, and product marketing strategy. This training was carried out by practitioners and experts in food processing and marketing. The results of this service show a significant increase in the community's knowledge and skills in processing squid into squid nuggets. Apart from that, there has been increased creativity, which can be seen from the various product innovations produced. Independent business groups were also formed, which could produce and market squid nuggets with consistent quality. Increasing community income from the squid nugget business is an indicator of the success of this program. In conclusion, the socialization program for making squid nuggets has succeeded in increasing coastal communities' creativity and economic welfare. However, to achieve long-term sustainability, it is necessary to pay attention to environmental aspects and expand the program's scope to widen its impact.